Cognitive Linguistic Approach to the Integrated Theory of Metaphor - MINIKEEVA, A.A; SADYKOVA, A.G.; MED, N.G. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The various aspects of metaphor and its application are on the agenda of this debate. This article has resources to dozens of European and American metaphor studies and presents the results of their analytical overview. As a result, this analysis depicts a range of topical issues. One of them is the development of a theory of metaphor that will integrate various approaches (linguistic, cognitive, communicative, and pragmatic) to the study of the metaphor, reproducing the change of a cognitive-linguistic approach to the figurative language analysis. Several theories about the cognitive aspect of matter have been introduced. RESUMEN Los diversos aspectos de la metáfora y su aplicación están en la agenda de este debate. Este artículo tiene recursos para docenas de estudios de metáforas europeas y americanas y presenta los resultados de su descripción analítica. Como resultado, este análisis describe una variedad de temas de actualidad. Uno de ellos es el desarrollo de una teoría de la metáfora que integrará varios enfoques (lingüísticos, cognitivos, comunicativos y pragmáticos) al estudio de la metáfora, reproduciendo el cambio de un enfoque cognitivo-lingüístico al análisis del lenguaje figurativo. Se han introducido varias teorías sobre el aspecto cognitivo de la materia.